Interdisciplinary Science Technology – Raman Spectroscopy to Meet the State and National Teaching Standards - Suzanne K. Lunsford (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Students need to be engaged into the lab with real-world instrumentation such as Raman spectroscopy which is highly needed into today's technological world. This study has engaged undergraduate students into problem solving the organic structure of various compounds /functional groups by utilizing i Raman spectroscopy instrumentation. The students understanding of abstract bonding concepts has been utilized by the FBI to solve and analyze unknowns /forensic chemistry compounds of interest. These experiences with the hands-on instrumentation have shown enhanced test scores in organic chemistry as well due to real-world bonding problems being resolved to analyze the unknown organic compounds by Raman spectroscopy.